Dalits and religion - Manohar, D. Murali (New Delhi : Atlantic Publishers & Distributors Pvt, Ltd, 2009)
Contributed articles presented at a national seminar held from 26-28 Oct. 2008 at School of Humanities, Dept. of English, University of Hyderabad in the Indian context.
Includes bibliographical references.
Keywords: Dalits -- India -- Religion -- Congresses; Dalits -- India -- Religious life -- Congresses